Analisis Resiko Keselamatan Kesehatan Kerja sebagai Upaya Pencegahan Kecelakaan dengan Menggunakan Metode Hazard Identification, Risk Assessment and Risk Control - Agung Joko Prasetyo; Widya Setiafindari (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2025)
PT MaduBaru PG/PS, a sugarcane agro-industry owned by the Sultanate of Ngayogyakarta Hadiningrat, faces a significant challenge in reducing workplace accidents. From January to September 2024, the company recorded 15 incidents, highlighting the need for a thorough analysis of potential hazards in its sugarcane processing operations. This study employs the HIRARC method (Hazard Identification, Risk Assessment, and Risk Control) to evaluate and address these risks. The hazards identified are categorized into low, medium, and high risks. Low-risk activities include kettle station work and rear factory cleaning tasks. Medium risks are found in kettle station cleaning, repair work, milling station operations, milling station cleaning, west DKS double work, and ash disposal site tasks. High-risk activities are primarily associated with Besali station operations. The main contributors to accidents are a lack of PPE usage, inadequate supervision, and non-compliance with SOPs, such as wearing non-standard footwear. The most dangerous incidents involve exposure to hot materials, which can be mitigated through the proper use of PPE. Enforcing SOP compliance and improving safety awareness are critical to reducing accidents. Strengthening safety measures and ensuring regular monitoring can help create a safer working environment at PT MaduBaru PG/PS.